Personality traits, coping strategies and nonspecific psychological distress: considerations for mental health in older adults - Garófalo, Carolina Sofía (2021)
Fil: Garófalo, Carolina Sofía. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina